Effect of dietary protein level and lamb breed on meat physicochemical traits, fatty acid profile and nutritional indices - H. Hajji; S. Smeti; I. Mekki; N. Atti (Archives Animal Breeding)
Special attention is increasingly given to food characteristics, particularly fatty acid (FA) profile. The quality of meat, as food of animal origin, depends on animal genotype and feeding. This study evaluated the meat quality and FA profile of three Tunisian sheep breeds, i.e. Barbarine (BB), Queue Fine de l'Ouest (QFO) and Noire de Thibar (NT), under diets with low (11 %) or high (16 %) crude protein (CP) levels, aiming to optimize feeding strategies for Tunisian sheep production. Lambs were slaughtered at 51 kg body weight. The longissimus-thoracis et lumborum muscle was extracted for meat quality analysis.